Perbandingan Hasil Refraksi Subjektif pada Jarak 6 Meter dan 4 Meter Menggunakan Slide Projector - Nugroho, Anggit; Farens Ferdinandus, Avita (stikes dharma husada bandung, 2021)
Refraction examination is identified as a measurement of refractive disorders. Refraction examination is divided into 2, namely objective and subjective refraction examinations. A subjective refraction examination is an examination that depends on the collaboration of the patient in assessing refraction the examination. Long distance subjective refraction checks generally use snellen chart at a distance of 6 meters. On the author's visit, it was found a checkpoint that was less than 4 meters using the snellen chart. Therefore, in this study the author aims to compare the results of subjective refraction at 6 meters and 4 meters with the method used cross sectional. The results showed that there were differences between the results subjective of refraction at a distance of 6 meters and 4 meters by 97 eyes from 104 eyes studied.